Consumer, prosumer, prosumager : how service innovations will disrupt the utility business model - Sioshansi, Fereidoon P. (Fereidoon Perry) (Academic Press, an imprint of Elsevier, 2019)
Consumers, Prosumers, Prosumagers: How Service Innovations will Disrupt the Utility Business Model examines customer stratification in the electric power sector, arguing that it is poised to become one of the fundamental drivers of the 21st century power network as distributed energy generation, storage, sharing and trading options become available at scale. The book addresses the interface and the relationship between key players and their impacts on incumbent and disruptive service providers. Topics covered include innovations that lead to consumer stratification, regulatory policy, the potential of service, the speed and spread of stratification, and a review of potential business models and strategies. The work also covers the evolution and potential end-states of electricity service provision, from its basis in current pilot programs as distributed generation scales and its potential to supplant industry norms.